Post-independence health research productivity in Portuguese-speaking African countries - Chissaque, Assucênio (2024)
Funding Information: L. G. was partially supported by the Foundation for Science and Technology, Portugal, through projects UIDB/Multi/04413/2020 and UIDP/Multi/04413/2020 (GHTM), UIDB/00006/2020 and UIDP/00006/2020 (CEAUL) and I. C. was partially supported by the Foundation for Science and Technology, Portugal, through projects UIDB/Multi/04413/2020 and UIDP/Multi/04413/2020 (GHTM). Publisher Copyright: © 2024 The Authors